Scientific Performance E-Rubric-Assisted Problem-based Learning for Improving Learning Effectiveness - Nur Hudha, Muhammad; Rahman Hakim, Arief; Dul Aji, Sudi; Ignasia Tasi, Maria; Sundaygara, Chandra; Pramudya Laksan, Eko; Andi, Tri; Candra Yusro, Andista; ., Hartoto; Anis Chaeruman, Uwes (International Journal of Engineering and Technology, 2018)
The use of online assessment nowadays has been increasingly necessary in the learning process. In relation to the statement, E-rubric is an online application that might be helpful in improving the learning effectiveness within the classroom. Then, in order to identify how the E-rubric might be helpful in such situation a study should be conducted in order to describe the use of Scientific Worksheet E-Rubric Problem-Based Learning for improving the Learning Effectiveness on the Heat topic. The study was a descriptive research that involved the students from Grade VII I and Grade VII J State Junior High Schools Academic Year 2017/2018 in the City of Malang. The results of the study show that most of the educators are satisfied with the presence of e-rubric application for assessing the studentsâ€™ scientific performance. Therefore, the use of e-rubric application is very helpful for improving the learning effectiveness within the learning process in the classroom.Â Â